Online mental health resources in Wuhan amid the COVID-19 pandemic: the role of social workers - Zhao, Kedi; Tan, Weijia; Tsang, A. Ka Tat (My University, 2022)
In Wuhan, a surge of online mental health services appeared amid the COVID-19 pandemic to meet the rapidly escalating demands. This article presents a snapshot of the available services and further categorises them into individual, organisational, governmental and international levels. The contribution and limitations of these services are analysed, and the role of social workers in the provision and integration of these services is reflected through a conceptual model. The proposed model as a response at this critical time not only facilitates the discussion on how mental health services in China should be adjusted and further developed in the post-COVID 19 era but also provides important strategies for other countries that are struggling with the delivery of mental health services amongst this public health crisis.
Keywords: psychological interventions; online mental health resources; social work services; Wuhan; COVID-19; conceptual model